PENGARUH MODEL ROLE PLAYING TERHADAP HASIL BELAJAR BAHASA INDONESIA DALAM TEMATIK DI SEKOLAH DASAR - Hertama, Sony Indra; Marli, Suhardi; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis The purpose of this research was to analyze the influence of the role playing learning models in Indonesia language lesson in thematic learning on student learning outcomes in fourth grade of Elementary School 31 West Pontianak. The research method used was an Experiment, a form ofQuasi Experimental type of NonEquivalent Control Group Design. The techniques used in data collection are measurements with research instruments in the form of multiplechoice test to measure cognitive domain, affective domain using attitude assessment sheets, and psychomotor domain using psychomotor assessment sheets. The sampling technique used Jenuh Sampling.The results of data analysis are, cognitive domain the average score of the learning outcomes experiment class 77,80 and the control class is 71,00. After the t-test is obtained tcount (3,682)> ttable(2,0042) then Ha is accepted. Affective domain the average score of the learning outcomes experiment class 75,46 and the control class is 75,33. After the t-test is obtained tcount (0,270) < ttable(2,0042) then Ho is accepted. Psychomotordomain the average score of the learning outcomes experiment class 75,46 and the control class is 73,30. After the t-test is obtained tcount (3,016) > ttable(2,0042) then Ha is accepted. From the calculation of the effect size obtained at 0.41 (medium criteria). This means that the role playing learning models has a influence on student learning outcomes in Indonesia language lesson in thematic learning in the fourth grade of Elementary School 31 West Pontianak.Keywords: Effect, Role Playing Models, Learning Outcomes